Implementation of Midwife Duties In Stand By Village By Kepmenkes No 564/Menkes/Sk/Viii/2006 About Guidelines of Implementation Stand by Village Related to Village Midwife Authority by Kepmenkes No 900/Menkes/SK/VII/2002 About Midwife Registration And - Erawati, Ambar Dwi (Jurnal Ilmu dan Teknologi Kesehatan, 2010)
Midwives perform services regulated by Kepmenkes No 900/Menkes/SK/VII/2002 about Midwife Registration and Practice in the form of authority. Along with standby village, midwives get additional tasks regulated in Kepmenkes No 564/Menkes/SK/VIII/2006 about Guidelines of Implementation Standby Village. Based on regulation above, formulation of the problem in this research are: 1. Is there any disagreement in the regulation, 2. How the form of legal protection for midwives in the standby village. This study aims to: 1. Comparing these two regulations, 2. Knowing the implementation of the practices of midwives in standby villages in Tuntang district Semarang Regency. Method used empiric juridical approach to the specific analysis descriptive. Object of this research there are 10 peopleâs midwives and confirmation with the Chairman of IBI center. Method of collecting data with interviews, observation and literature study. Results of research there are disagreement and the differences between the two regulations. Kepmenkes No 900/Menkes/SK/VII/2002 about Midwife Registration and Practice are rules of Minister of Health regulating the authority of the midwife in providing midwifery services to the mother, child and family planning program. Outside the service aims to save lives. Kepmenkes No 564/Menkes/SK/VIII/2006 about Guidelines of Implementation Standby Village is rules of Minister of Health regulating the task of midwives to provide basic medical services to the community. Midwife in stand by village fulfill all duty which is decanted in Kepmenkes No 564. Midwife in Tuntang District Stand by Village in executing midwife standby village duties is protected by Criminal Low Book (KUH Pidana). Keywords: authority, duties, regulation, decree, Kepmenkes No 900/Menkes/SK/VII/2002 about Midwife Registration and Practice, Kepmenkes No 564/Menkes/SK/VIII/2006 about Guidelines of Implementation Standby Village.